Stability and Data Dependence Results for Jungck-type Iteration Scheme (Contemporary Mathematics, 2024)
We propose and study a new Jungck-type iteration scheme to approximate coincidence points of contractive mappings. The strong convergence, stability, and data dependency results have been discussed. Numerical experiments demonstrate that the newly introduced Jungck-type iteration scheme yields a higher convergence rate in comparison with other Jungck-type iteration schemes available in the literature.
Keywords: strong convergence; non-linear equation; Banach space; contraction-type mappings